Sporadic cases of acute autochthonous hepatitis E virus infection in Southwest Germany - Brost, Sylvia; Wenzel, J. J.; Ganten, Tom M.; Filser, Michael; Flechtenmacher, Christa; Boehm, S.; Astani, Akram; Jilg, W.; Zeier, Martin; Schnitzler, Paul (Clinical and diagnostic virology, 2010)
Hepatitis E infection is usually a self-limiting disease and an important cause of acute hepatitis in tropical and subtropical regions where the virus is endemic. In industrialized countries, sporadic cases of acute hepatitis E virus (HEV) infections have been described and the number of documented autochthonous infections seems to be increasing. We report three sporadic cases of autochthonous hepatitis E infections in Southwestern Germany which presented at our university hospital within two years. All cases were men who presented with acute hepatitis, icterus and elevated liver. In case 1 and case 2, liver biopsy revealed acute hepatitis, both patients were positive for anti-HEV antibodies, case 1 was also positive for HEV RNA with a viral load of 3.0×103copies/ml in serum. In case 3, anti-HEV antibodies were detectable and HEV RNA was detected in serum (4.3×103copies/ml) and stool (1.4×106copies/ml). None of the patients had a recent travel history outside Germany and close contact to animals has been denied. HEV sequence analysis of two patients revealed genotype 3 with homologies to other European isolates and isolates from swine. Thus the source of infection remains unclear. Hepatitis E should be considered in differential diagnosis in patients with unexplained hepatitis and patients with acute hepatitis, whatever their age or travel history might be, should be tested for HEV.